Analisis Forensik Aplikasi Michat Menggunakan Metode Digital Forensics Research Workshop (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
The development of information technology has had various positive and negative effects. The positive impact that information technology can have is to make it easier for people to communicate with others in the world, and the negative impact is that society is out of control when using its applications. It is an attitude that causes various crimes in the world caused by cyberspace (cybercrime) One of the most widely used instant messaging applications is Michat. The MiChat app causes cybercrime, pornography, online gambling, fraud, cyberbullying and drug trafficking. Evidence research is conducted using one of the frameworks of the digital forensic research workshop. In this framework, forensic identification, preservation, collection, investigation, analysis, and presentation phases are designed to find evidence of digital crime. The forensic tools used to collect evidence are mobility forensic express pro, a DB browser for SQLite, and oxygen forensic detective. Results are presented in the form of reports and evidence, and text chat files, contacts, images, audio, video, and web caches are generated. Forensic tools have a 100% success rate in finding evidence. Comparing the functions of the three forensic tools, the mobility forensic express pro has a processing rate of 66.7%, DB browser for SQLite has 33.3%, and oxygen forensic detective has 83.3%. Digital evidence can be used as corroborating evidence in a trial